The Effect of Academic Background and Religious Orientation to Religious Fundamentalism among University Students - Fihris, Fihris (FITK UIN Walisongo, 2020)
This paper discusses influence of the religious orientation and educational background of students to fundamentalism. This study involved 291 students of the UIN Walisongo and Diponegoro University (UNDIP). Data were collected using a Likert scale questionnaire and analyzed by multiple regression. The results showed that religious orientation significantly affected student religious fundamentalism with value of f = 17.523. On the other hand, educational background does not significantly affect student religious fundamentalism with a value of f = 2.430. Likewise, the interaction of religious orientation and educational background did not significantly affect student religious fundamentalism with a value of f = 10.010.Â AbstrakPenelitian ini membahas pengaruh orientasi agama dan latar belakang pendidikan mahasiswa terhadap fundamentalisme agama. Penelitian ini melibatkan 291 mahasiswa Universitas Islam Negeri (UIN) Walisongo dan Universitas Diponegoro (UNDIP). Data dikumpulkan dengan menggunakan kuesioner skala likert dan dianalisis dengan regresi ganda. Hasil penelitian menunjukkan bahwa orientasi keagamaan signifikan mempengaruhi fundamentalisme agama pada mahasiswa dengan nilai f = 17,523. Sebaliknya latar belakang pendidikan tidak signifikan mempengaruhi fundamentalisme agama pada mahasiswa dengan nilai f = 2,430. Demikian juga interaksi orientasi keagamanan dan latar belakang pendidikan tidak signifikan mempengaruhiÂ fundamentalisme agama pada mahasiswaÂ dengan nilai f = 10,010.